PENGARUH SALES GROWTH, LEVERAGE, LIKUIDITAS, ARUS KAS OPERASI DAN KEPEMILIKAN MANAJERIAL TERHADAP FINANCIAL DISTRESS - Safa Shinta Kinanti; Regina Jansen Arsjah (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the effect of sales growth, leverage, liquidity, operating cash flow, and managerial ownership on financial distress in companies in the hotel, restaurant, tourism, and textile sub-sectors listed on the Indonesia Stock Exchange (IDX) during the period 2021–2024. The research sample was selected using purposive sampling, with specific criteria resulting in 80 observations from 20 companies. The data used were secondary data obtained from the IDX official website and each company. The analysis was conducted using panel data regression to test the simultaneous and partial effects between variables. The results indicate that sales growth does not significantly influence financial distress. Meanwhile, leverage and liquidity have a negative effect, while operating cash flow and managerial ownership have a positive effect on financial distress. These findings have strategic implications within the framework of agency theory, where managerial ownership can strengthen oversight and reduce the risk of financial distress. For regulators, these results support the need for transparency policies regarding internal indicators such as liquidity and cash flow to strengthen early warning systems against potential corporate financial failure